AÇÃO CITOTÓXICA DO AGROTÓXICO 2,4 D EM LEVEDURAS - SARABIA, Débora Tavares; MUELLER, Larissa Pires; MASCARENHAS SANTOS, Maria do Socorro; SURIANO, Ezequiel Marques; SILVA, Rebeca Fasioli; BATISTOTE, Margareth (ANAIS DO ENIC, 2020)
-